A Cross-Sectional Survey of the North American Skull Base Society Part 3: The State of Lateral Skull Base Surgery Training in North America - Patel, Neil S.; Gompel, Jamie J. Van; Tombers, Nicole M.; Link, Michael J.; Carlson, Matthew L. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Introduction Optimal management of vestibular schwannoma (VS) demands involvement of an experienced multidisciplinary team. As the number of training programs in neurotology and skull base neurosurgery continues to rise, ensuring that trainees are capable of evidence-based decision-making and treatment, whether microsurgical or radiosurgical, is of paramount importance. The purpose of this study is to characterize the landscape of neurotologic and neurosurgical fellowship training programs in North America, with special reference to VS management.Methods A 64-item web-based survey assessing VS practice trends was devised by members of the North American Skull Base Society (NASBS) Research Task Force and distributed electronically to NASBS membership via SurveyMonkey as a cross-sectional study. Participation was entirely voluntary and there was no remuneration for survey completion. The survey link was active from November 29 to December 14, 2016.Results Of 719 members of the NASBS who were emailed a survey link, a total of 57 were returned (8%) completed surveys. Of all respondents, 51 (89%) claimed to have formal training in skull base neurosurgery or neurotology. Thirty-three respondents (65%) were skull base neurosurgeons while the remainder were neurotologists (n = 18; 35%). Institutions with fellowship programs tended to have a higher surgical, radiosurgical, and overall case volume than those with a residency program alone. However, 20% of respondents at institutions with fellowship programs reported evaluating less than 50 new diagnoses of VS per year and 12% reported a surgical case volume of less than 10 cases per year.Conclusion As the number of skull base training programs expands, it is our duty to ensure that trainees gain sufficient experience to enter independent practice with the ability to exercise informed decision-making and safely perform VS surgery and radiosurgery. In the current training climate, implementing multidisciplinary care models, formalized training requirements, and emerging surgical simulators will support the development of minimum proficiencies in VS care.
Keywords: vestibular schwannoma; acoustic neuroma; skull base surgery; cranial base surgery; microsurgery; radiosurgery